Yield stress and elasticity influence on surface tension measurements. Issue 25 (7th July 2015) - Jørgensen, Loren; Le Merrer, Marie; Delanoë-Ayari, Hélène; Barentin, Catherine
<x xml:space="preserve">Abstract</x> Surface tension measurements are challenged by jamming in yield stress fluids, even at small scales. However our setup allowing opposite directions in deformation provides a method to deal with elastoplastic forces and measure the surface tension of yield stress fluids.